2006
DOI: 10.1029/2005jd006778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Global Ozone Monitoring Experiment (GOME) ozone profiles from nine different algorithms

Abstract: [1] An evaluation is made of ozone profiles retrieved from measurements of the nadir-viewing Global Ozone Monitoring Experiment (GOME) instrument. Currently, four different approaches are used to retrieve ozone profile information from GOME measurements, which differ in the use of external information and a priori constraints. In total nine different algorithms will be evaluated exploiting the optimal estimation (Royal Netherlands Meteorological Institute, Rutherford Appleton Laboratory, University of Bremen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 72 publications
(101 reference statements)
0
32
0
Order By: Relevance
“…As for SBUV, Optimal Estimation techniques (Rodgers, 2000) are used for the retrievals. GOME ozone profiles were extensively analyzed by Meijer et al (2006) and when the OMI measurements became available these were validated by Kroon et al (2011).…”
Section: Gome/gome-2mentioning
confidence: 99%
“…As for SBUV, Optimal Estimation techniques (Rodgers, 2000) are used for the retrievals. GOME ozone profiles were extensively analyzed by Meijer et al (2006) and when the OMI measurements became available these were validated by Kroon et al (2011).…”
Section: Gome/gome-2mentioning
confidence: 99%
“…Over the years, several groups, have developed physically based retrieval algorithms to retrieve ozone profiles from GOME radiances (Munro et al, 1998;Hoogen et al, 1999;Hasekamp and Landgraf, 2001;van der A et al, 2002;Liu et al, 2005). Meijer et al (2006) evaluated ozone profiles retrieved from these algorithms and concluded that, though ozone profiles can be retrieved from GOME with better information content in the lower stratosphere than that from Solar Backscatter Ultraviolet (SBUV) instruments, they were not able to demonstrate robust determination of tropospheric ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Because these instruments measure BUV radiances only at 12 discrete wavelength bands in the range of 256-340 nm, the information on ozone vertical distribution is limited to 20-50 km (Bhartia et al, 1996). With the launch of UV/visible spectrometers such as the Global Ozone Monitoring Experiment (GOME) (ESA, 1995), which take BUV radiance spectra at moderate spectral resolution, the retrieval of vertical ozone profiles can be extended down to the troposphere (Chance et al, 1997;Meijer et al, 2006 and references therein). Liu et al (2005) developed an optimal estimation (OE)-based algorithm to retrieve ozone profiles including tropospheric ozone from GOME BUV radiance spectra.…”
Section: Introductionmentioning
confidence: 99%